All-solid-state polymer electrolyte and preparation method and application thereof

CN116646593BActive Publication Date: 2026-10-20SHAOXING INST OF NEW ENERGY & MOLECULAR ENG SHANGHAI JIAO TONG UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310534209.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-12
Publication Date
2026-10-20
Estimated Expiration
2043-05-12

AI Technical Summary

Technical Problem

然而,全固态钠离子电池仍然面临着离子电导率低,钠离子迁移数小、循环稳定性差等问题

Benefits of technology

[0040](1)本发明提供了一种全固态聚合物电解质,该全固态聚合物电解质实现了离子传导率、钠离子迁移数、电化学稳定性等综合性能的同步提升,满足全固态钠离子电池的实际应用需求。通过实验和检测分析,本发明的全固态聚合物电解质具有良好的电化学性能:(1)离子传导率为2×10-4~6×10-4S cm-1,优选为5×10-4~6×10-4S cm-1;(2)钠离子迁移数大于0.28,优选为0.5-0.9;(3)电化学窗口大于3.8V vs.Na+/Na,优选为5.0V~6.0Vvs.Na+/Na,且所述全固态聚合物电解质对金属钠具有良好的稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116646593B_ABST
    Figure CN116646593B_ABST
Patent Text Reader

Abstract

The application discloses a kind of all-solid-state polymer electrolyte and its preparation method and application, it is related to sodium ion battery field, it is characterized in that: the all-solid-state polymer electrolyte includes functional matrix, polymer matrix and sodium salt, wherein, the functional matrix includes boron-containing organic structure and porous support body, functional matrix is obtained by in-situ growth of boron-containing organic structure on the surface of porous support body, the boron-containing organic structure has abundant Lewis acid sites;The application provides an all-solid-state polymer electrolyte, the all-solid-state polymer electrolyte realizes the synchronous promotion of ion conductivity, sodium ion transference number, electrochemical stability and the like comprehensive performance, the all-solid-state polymer electrolyte prepared by the application has unique composition and structure, the electrolyte can simultaneously enhance the interface stability of positive electrode / electrolyte and negative electrode / electrolyte, and the assembled all-solid-state sodium ion battery has good rate performance and cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of sodium-ion batteries, specifically to an all-solid-state polymer electrolyte, its preparation method, and its application. Background Technology

[0002] Developing efficient and cost-effective energy storage devices is one of the most effective ways to solve the current energy shortage and low utilization rate problems. Among various energy storage devices, lithium batteries, as typical rechargeable batteries, have received extensive research. However, the scarcity of lithium resources has led to a continuous increase in the cost of lithium batteries, severely limiting their development. Sodium, which belongs to the same group as lithium, has similar physicochemical properties to lithium. Sodium-ion batteries not only have high safety and adaptability, but research also shows that sodium-ion batteries have excellent high and low temperature performance. Furthermore, benefiting from the wide distribution and low cost of sodium resources, sodium-ion batteries are expected to have wider and deeper applications in certain fields, especially in large-scale energy storage. However, currently reported sodium-ion batteries mainly use flammable and volatile organic electrolytes, which are prone to serious safety accidents due to thermal runaway during battery use. On the other hand, organic electrolytes have a narrow electrochemical window and are unstable with metallic sodium, making it difficult to match high-voltage positive electrodes and metallic sodium negative electrodes, which severely limits the improvement of the energy density of sodium-ion batteries.

[0003] Replacing organic electrolytes with solid-state electrolytes to construct solvent-free all-solid-state sodium-ion batteries not only solves the aforementioned problems, but also allows for a wider range of anode material selection due to the stable contact interface, thus enabling the selection of sodium-ion batteries with high safety and high energy density. However, all-solid-state sodium-ion batteries still face challenges such as low ionic conductivity, low sodium ion transport number, and poor cycle stability. Therefore, developing high-performance all-solid-state electrolytes is a major technical challenge for realizing the commercial application of sodium-ion batteries. Summary of the Invention

[0004] Therefore, a first aspect of the present invention aims to provide an all-solid polymer electrolyte that simultaneously possesses high ionic conductivity, high sodium ion transport number, excellent mechanical properties, and good stability to metallic sodium.

[0005] The technical solution adopted in this invention is as follows:

[0006] An all-solid polymer electrolyte, characterized in that: the all-solid polymer electrolyte comprises a functional matrix, a polymer matrix, and a sodium salt, wherein the functional matrix comprises a boron-containing organic structure and a porous support, and the boron-containing organic structure has abundant Lewis acid sites.

[0007] Further settings include:

[0008] The polymer matrix includes ethoxy groups, and the polymer matrix is ​​combined with sodium salt and then infused into the functional matrix.

[0009] The polymer matrix is ​​preferably an ether polymer, and more preferably, the polymer is at least one of polyethylene oxide (PEO) and polyphenylene ether (PPO).

[0010] The sodium salt is selected from sodium salts suitable for ether-based electrolytes, and particularly preferably, the sodium salt is selected from at least one of NaClO4, NaPF6, NaFSI, NaTFSI, and NaBF4.

[0011] The functional matrix is ​​a porous support modified with a boron-containing organic structure, which is obtained by in-situ growth of the boron-containing organic structure on the surface of the porous support.

[0012] The porous support is selected from porous supports with abundant continuous fiber pores, preferably at least one of glass fiber membrane, polyimide membrane, cellulose nonwoven membrane, polyethylene terephthalate film, and polyimide membrane.

[0013] The boron-containing organic structure is selected from any of the compounds having the following structural formulas:

[0014]

[0015]

[0016]

[0017] A second aspect of the present invention is to provide a method for preparing the above-mentioned all-solid polymer electrolyte, characterized in that: a functional matrix is ​​prepared by solution in-situ polymerization using a porous support as a substrate, the polymer matrix and sodium salt mixed solution are injected into the functional matrix, and finally the all-solid polymer electrolyte is obtained by vacuum hot pressing and drying.

[0018] Furthermore:

[0019] A method for preparing the above-mentioned all-solid-state polymer electrolyte, characterized by comprising the following steps:

[0020] (1) Preparation of functional matrix:

[0021] Boron-containing monomers and ligands are mixed into a solvent to form a precursor mixture. The porous support is then immersed in the precursor mixture and polymerized in situ to obtain a porous support modified with a boron-containing organic structure, which is the functional matrix.

[0022] (2) Preparation of composite all-solid polymer electrolyte membrane:

[0023] The polymer matrix and sodium salt are prepared into a solution in a certain proportion and filled into the functional matrix obtained in step (1) by solution perfusion method to obtain a composite all-solid polymer electrolyte membrane.

[0024] (3) Vacuum hot pressing drying treatment:

[0025] The composite all-solid polymer electrolyte membrane prepared in step (2) is placed in a button mold and subjected to vacuum drying to obtain the all-solid polymer electrolyte.

[0026] The inventors discovered that by adjusting the ratio of the precursor mixture solution, the in-situ polymerization reaction time and / or the temperature during the in-situ polymerization reaction, the ratio of polymer matrix to sodium salt, the vacuum hot-pressing load and / or temperature, etc., the physical and electrochemical properties of the all-solid-state polymer electrolyte can be further controlled, as follows:

[0027] In step (1), the boron-containing monomer is selected from any one of 1,4-phenyldiboronic acid (BDBA), biphenyl diboronic acid (BPDA), 1,3,5-phenyltriboronic acid (BTBA), and 1,3,5-phenyl ester (4-phenylboronic acid) (BTPA).

[0028] In step (1), the ligand is selected from any one of 1,4-phenyldiboronic acid (BDBA) and 2,3,6,7,10,11-hexahydroxytriphenyl (HHTP).

[0029] In step (1), the solvent is a mixed solution of m-trimethylbenzene and 1,4-dioxane, and the volume ratio of m-trimethylbenzene to 1,4-dioxane is 0.5-1.5:0.5-1.5, preferably 0.8-1.2:0.8-1.2, and more preferably 1:1.

[0030] In step (1), the reaction temperature of the in-situ polymerization is 100℃~150℃, more preferably 120℃.

[0031] In step (1), the in-situ polymerization reaction takes 24h to 96h, more preferably 72h.

[0032] In step (1), the product obtained from the in-situ polymerization reaction is washed, activated, vacuum dried, and then sealed for storage. Anhydrous acetone or anhydrous acetonitrile is used as the washing solvent, preferably anhydrous acetone, and the washing is performed 1-4 times, preferably 3 times. Anhydrous acetone is used as the activation solvent, and the activation time is 12-36 hours, preferably 24 hours. The vacuum drying temperature is 100℃-150℃, preferably 120℃, and the vacuum drying time is 12-36 hours, preferably 24 hours. The prepared functional matrix is ​​sealed and stored in an inert atmosphere to prevent hydrolysis.

[0033] In step (2), the polymer matrix is ​​PEO or PPO, preferably PEO.

[0034] In step (2), the sodium salt is selected from NaClO4, NaPF6, NaFSI, NaTFSI or NaBF4, preferably NaTFSI.

[0035] In step (2), the ratio of the polymer matrix to the sodium salt is 8 to 20:1, preferably 16:1.

[0036] In step (3), the load pressure of the snap mold is 5-50N, preferably 20N, and the vacuum drying temperature is 50-80℃, preferably 60℃.

[0037] A third aspect of this invention aims to provide the application of the above-described all-solid-state polymer electrolyte in the preparation of all-solid-state sodium-ion batteries. Specifically, an all-solid-state sodium-ion battery includes a positive electrode, a negative electrode, and the above-described all-solid-state polymer electrolyte.

[0038] In this invention, there are no specific limitations on the positive and negative electrodes of the all-solid-state sodium-ion battery; any positive and negative electrode materials known in this technical field can be used. Exemplarily, the positive electrode includes at least one of sodium vanadium phosphate, sodium nickel iron manganese oxide, Prussian blue, sodium ion fluorophosphate, sodium iron sulfate, and sodium vanadium fluorophosphate. Exemplarily, the negative electrode contains at least one of metallic sodium, molybdenum disulfide, hard carbon, sodium titanium oxide, nickel cobalt oxide, antimony oxide, and antimony-carbon composite materials.

[0039] The beneficial effects of this invention are:

[0040] (1) This invention provides an all-solid-state polymer electrolyte, which achieves simultaneous improvement in comprehensive performance such as ionic conductivity, sodium ion transport number, and electrochemical stability, meeting the practical application requirements of all-solid-state sodium-ion batteries. Through experiments and testing analysis, the all-solid-state polymer electrolyte of this invention has good electrochemical performance: (1) Ionic conductivity is 2×10 -4 ~6×10 -4 S cm -1 Preferably 5×10 -4 ~6×10 -4 S cm -1 (2) Sodium ion transference number greater than 0.28, preferably 0.5-0.9; (3) Electrochemical window greater than 3.8V vs. Na + / Na, preferably 5.0V~6.0V vs. Na + / Na, and the all-solid polymer electrolyte has good stability against metallic sodium.

[0041] The reasons for this are as follows: Firstly, the electrolyte of this invention can utilize the trapping effect of boron-containing organic structures on anions, effectively increasing the sodium ion transport number while promoting sodium salt dissociation and reducing concentration polarization caused by charge transfer within the electrolyte, thereby stabilizing the sodium deposition and stripping process at the negative electrode / electrolyte interface. Secondly, by adopting an in-situ growth strategy, the boron-containing organic structures are distributed uniformly to the maximum extent on a porous support with a regular fibrous skeleton, fully utilizing their functionality while also constructing a rapid sodium ion transport channel, thus enabling the all-solid-state sodium-ion battery to exhibit good cycle stability and rate performance.

[0042] (2) The present invention provides a method for preparing an all-solid polymer electrolyte. In this method, the main material of the all-solid polymer electrolyte (mainly composed of boron-containing organic structure and porous support) is inexpensive and low-cost. Furthermore, the preparation process of the all-solid polymer electrolyte of the present invention is simple, safe, and environmentally friendly.

[0043] (3) The present invention provides an application of an all-solid polymer electrolyte in the preparation of an all-solid sodium-ion battery. The all-solid polymer electrolyte of the present invention has a unique composition and structure. The electrolyte can simultaneously enhance the stability of the positive electrode / electrolyte interface and the negative electrode / electrolyte interface. The assembled all-solid sodium-ion battery has good rate performance and cycle stability.

[0044] The present invention will be further described below with reference to the accompanying drawings and specific embodiments. Attached Figure Description

[0045] Figure 1 Scanning electron microscope image (a) of B-GF prepared for Example 1 and image (b) of B-GF after ultrasonic exfoliation.

[0046] Figure 2 Scanning electron microscope (SEM) image of the electrolyte SCPE prepared in Example 1.

[0047] Figure 3 Energy dispersive spectroscopy (EDS) of the electrolyte SCPE prepared in Example 1.

[0048] Figure 4 The image shows an X-ray diffraction (XRD) pattern of the electrolyte SCPE prepared in Example 1.

[0049] Figure 5 Fourier transform infrared (FT-IR) spectra of the electrolyte SCPE prepared in Example 1.

[0050] Figure 6 Impedance spectrum of ionic conductivity test of the electrolyte SCPE prepared in Example 1.

[0051] Figure 7 Electrochemical window testing of the electrolyte SCPE prepared in Example 1.

[0052] Figure 8 DC polarization curve (a) and impedance spectrum (b) of sodium ion transport number test for the electrolyte SCPE1 prepared in Example 1.

[0053] Figure 9 Scanning electron microscope image of B-GF prepared in Example 2.

[0054] Figure 10 Scanning electron microscope image of B-GF prepared in Example 3.

[0055] Figure 11 The image shows a scanning electron microscope image of B-GF prepared in Example 4.

[0056] Figure 12 Scanning electron microscope image of B-GF prepared in Example 5.

[0057] Figure 13 Scanning electron microscope image of B-GF prepared for Comparative Example 2.

[0058] Figure 14 Scanning electron microscope image of B-GF prepared for Comparative Example 3.

[0059] Figure 15 Scanning electron microscope image of B-GF prepared for Comparative Example 4.

[0060] Figure 16 Scanning electron microscope image of B-GF prepared for Comparative Example 5.

[0061] Figure 17 The charge-discharge curves of the all-solid-state sodium-ion battery in Application Example 1 are shown.

[0062] Figure 18 The graph shows the cycle performance of the all-solid-state sodium-ion battery in Application Example 1.

[0063] Figure 19 The above is a charge-discharge curve of the all-solid-state sodium-ion battery for Comparative Example 2.

[0064] Figure 20 The graph shows the cycle performance of the all-solid-state sodium-ion battery in Comparative Example 2. Detailed Implementation

[0065] The technical solution of the present invention will be further described in detail below with reference to specific embodiments. It should be understood that the following embodiments are merely illustrative and explanatory of the present invention, and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are covered within the scope of protection intended by the present invention.

[0066] Unless otherwise stated, the raw materials and reagents used in the following examples are commercially available products or can be prepared by known methods.

[0067] Example 1: Preparation of all-solid-state polymer electrolyte SCPE

[0068] The preparation method of the all-solid-state polymer electrolyte SCPE is as follows:

[0069] (1) Preparation of functional matrix membrane B-GF:

[0070] 0.1 g of glass fiber membrane GF, 0.25 g of BDBA, and 10 mL of a 1:1 m-trimethylbenzene:1,4-dioxane solution were sealed in a Schlenk flask and sonicated at room temperature for 60 minutes. The resulting suspension was then rapidly frozen at 77 K (LN2 bath) and evacuated. The mixture was then thawed by sonication, and this process was repeated twice to completely remove residual air. The prepared mixture was placed at 120 °C for 72 hours to obtain an in-situ grown COF-1 fiber membrane. This membrane was washed with anhydrous acetone (treated with molecular sieves), activated with anhydrous acetone for 24 hours, and then dried in a vacuum oven at 120 °C for 12 hours to obtain the functional matrix membrane B-GF. The obtained functional matrix membrane B-GF was sealed and stored in a glove box for later use to prevent hydrolysis.

[0071] (2) Preparation of composite all-solid polymer electrolyte membrane ex-SCPE:

[0072] First, polymer PEO (0.064 mol) and NaTFSI (0.004 mol) were dissolved in 20 mL of anhydrous acetonitrile to form a transparent homogeneous solution. The PEO / Na... + The molar ratio was controlled at 16:1. Subsequently, the functional matrix membrane B-GF synthesized in step (1) was placed in a polytetrafluoroethylene mold, and the above solution was injected into the functional matrix membrane B-GF. The acetonitrile was allowed to evaporate naturally to obtain the composite all-solid polymer electrolyte membrane ex-SCPE, which was then stored in an inert atmosphere.

[0073] (3) Preparation of all-solid polymer electrolyte SCPE:

[0074] In a glove box, the composite all-solid polymer electrolyte membrane ex-SCPE prepared in step (2) is placed in a button-type polytetrafluoroethylene mold, and after applying a load of 20N, it is moved into a vacuum drying oven and dried at 60°C for 12 hours to finally obtain the all-solid polymer electrolyte SCPE.

[0075] Product testing:

[0076] 1. Product morphology and composition

[0077] The microstructure of the functional matrix B-GF was observed using scanning electron microscopy (SEM), and the results are as follows: Figure 1 As shown in figure a, the boron-containing organic structure COF-1 exhibits a densely packed structure on the surface of glass fibers. Furthermore, through... Figure 1 b shows that COF-1 exhibits a layered structure and is distributed close to the glass fiber, proving that the boron-containing organic structure COF-1 was successfully grown in situ on the fiber surface of the porous support GF.

[0078] The microstructure of the all-solid-state polymer electrolyte SCPE was observed using scanning electron microscopy (SEM), and the results are as follows: Figure 2 As shown: The all-solid polymer electrolyte SCPE exhibits a smooth and uniform surface.

[0079] The structural composition of the all-solid-state polymer electrolyte SCPE was observed using energy-dispersive spectroscopy (EDS), and the results are as follows: Figure 3 As shown, the C, N, and O contained in polymer PEO, the Na, F, and S contained in NaTFSI, and the B and Si contained in B-GF are all uniformly distributed in the cross-section of the prepared all-solid polymer electrolyte SCPE, indicating a good composite of polymer PEO, NaTFSI, and B-GF.

[0080] The structural composition of the all-solid-state polymer electrolyte SCPE was investigated using X-ray diffraction (XRD), and the results are as follows: Figure 4 As shown, the all-solid polymer electrolyte SCPE exhibits characteristic peaks of polymer PEO, NaTFSI, and boron-containing organic structure COF-1, proving that the all-solid polymer electrolyte SCPE is composed of polymer PEO, NaTFSI, and boron-containing organic structure COF-1.

[0081] The structure and composition of the all-solid-state polymer electrolyte SCPE were verified using Fourier transform infrared spectroscopy (FT-IR), and the results are as follows: Figure 5 As shown: Figure 5 As shown in a, the boron-containing organic structure COF-1 is grown in situ on B-GF. Through... Figure 5 As can be seen from b, the boron-containing organic structure COF-1 grows in situ on the porous support GF. Furthermore, through... Figure 5c and 5d show the presence of polymer PEO in the all-solid polymer electrolyte SCPE.

[0082] 2. Electrical performance testing of all-solid-state polymer electrolyte SCPE

[0083] 2.1 Ionic conductivity of the all-solid-state polymer electrolyte SCPE:

[0084] The electrolyte SCPE prepared in this embodiment was sandwiched between two stainless steel sheets and assembled in a 2032 battery case. Electrochemical impedance spectroscopy was performed using an electrochemical workstation. The ionic conductivity of the electrolyte was calculated using the following formula:

[0085]

[0086] Where L is the thickness of the all-solid polymer electrolyte, S is the area of ​​the stainless steel sheet facing each other, and R... b The measured electrolyte bulk impedance is shown below. The test results are as follows: Figure 6 As shown, the ionic conductivity of the electrolyte SCPE in Example 1 at 60°C is 5.48 × 10⁻⁶. -4 S cm -1 .

[0087] 1.2 Electrochemical window of all-solid-state polymer electrolyte SCPE:

[0088] The all-solid-state polymer electrolyte SCPE was sandwiched between a stainless steel sheet and a sodium sheet and assembled in a 2032 battery case. Linear voltammetry was performed using an electrochemical workstation to measure the electrochemical window under the following conditions: onset potential of 2V, maximum potential of 6.5V, and scan rate of 5mV / s. The results are as follows: Figure 7 As shown, the electrochemical window of the bifunctional gel polymer electrolyte in Example 1 is 5.98 V vs. Na. + / Na.

[0089] 1.3 Na of the all-solid-state polymer electrolyte SCPE + Number of migrations

[0090] A Na / SCPE / Na symmetric cell was assembled in a 2032 battery case by sandwiching the all-solid-state polymer electrolyte SCPE between two sodium plates. The sodium ion transport number was measured using AC impedance spectroscopy and potentiostat chronoamperometry. The polarization voltage is 10 mV. The sodium ion transport number can be calculated using the following formula:

[0091]

[0092] Where I0 and I SThe current values ​​before and after polarization are R0 and R, respectively. S The figures show the interface impedances before and after polarization, respectively, with ΔV representing the applied polarization voltage. The test results are as follows: Figure 8 As shown, the sodium ion transference number of the all-solid polymer electrolyte prepared in Example 1 is 0.62.

[0093] Example 2

[0094] The preparation method of the all-solid-state polymer electrolyte SCPE is as follows:

[0095] (1) Preparation of functional matrix membrane B-GF:

[0096] 0.1 g of glass fiber membrane GF, 0.25 g of BDBA, and 10 mL of a 1:1 m-trimethylbenzene:1,4-dioxane solution were sealed in a Schlenk flask and sonicated at room temperature for 60 minutes. The resulting suspension was then rapidly frozen at 77 K (LN2 bath) and evacuated. The mixture was then thawed by sonication, and this process was repeated twice to completely remove residual air. The prepared mixture was placed at 100 °C for 72 hours to obtain an in-situ grown 3D fiber framework of COF-1, which was then washed with anhydrous acetone (treated with molecular sieves). The resulting fiber membrane was activated with anhydrous acetone for 24 hours and then dried in a vacuum oven at 100 °C for 12 hours to obtain a functional matrix membrane. The resulting white fiber membrane (i.e., B-GF) was sealed and stored in a glove box for later use to prevent hydrolysis.

[0097] (2) Preparation of composite all-solid polymer electrolyte membrane ex-SCPE:

[0098] First, polymer PEO (0.064 mol) and NaTFSI (0.004 mol) were dissolved in 20 mL of anhydrous acetonitrile to form a transparent homogeneous solution. The PEO / Na... + The molar ratio was controlled at 16:1. Subsequently, the functional matrix B-GF synthesized in step (1) was placed into a polytetrafluoroethylene mold, and the above solution was injected into B-GF. The acetonitrile was allowed to evaporate naturally, thereby obtaining a preliminary all-solid polymer electrolyte membrane ex-SCPE, which was then stored in an inert atmosphere.

[0099] (3) Vacuum hot-pressing and drying process for preparing all-solid polymer electrolyte SCPE:

[0100] In a glove box, the ex-SCPE prepared in step (2) was placed in a button-type polytetrafluoroethylene mold, and after applying a load of 20N, it was moved into a vacuum drying oven and dried at 60°C for 12 hours to finally obtain the all-solid polymer electrolyte SCPE.

[0101] Product testing:

[0102] like Figure 9 As shown, the B-GF prepared in Example 2 can grow boron-containing organic structures in situ on the surface of glass fibers, but the boron-containing organic structures exhibit irregular and uneven morphology.

[0103] The ionic conductivity, electrochemical window, and sodium ion transference number of the all-solid-state polymer electrolyte SCPE prepared in Example 2 were tested using the test method described in Example 1. The ionic conductivity of the all-solid-state polymer electrolyte SCPE prepared in Example 2 at 60°C was measured to be 3.42 × 10⁻⁶. -4 S cm -1 The electrochemical window is 5.68V vs. Na. + / Na, sodium ion transference number is 0.52.

[0104] Example 3

[0105] The preparation method of the all-solid-state polymer electrolyte SCPE is as follows:

[0106] (1) Preparation of functional matrix membrane B-GF:

[0107] 0.1 g of glass fiber membrane GF, 0.25 g of BDBA, and 10 mL of a 1:1 m-trimethylbenzene:1,4-dioxane solution were sealed in a Schlenk flask and sonicated at room temperature for 60 minutes. The resulting suspension was then rapidly frozen at 77 K (LN2 bath) and evacuated. The mixture was then thawed by sonication, and this process was repeated twice to completely remove residual air. The prepared mixture was placed at 150 °C for 72 hours to obtain an in-situ grown 3D fiber framework of COF-1, which was then washed with anhydrous acetone (treated with molecular sieves). The resulting fiber membrane was activated with anhydrous acetone for 24 hours and then dried in a vacuum oven at 150 °C for 12 hours to obtain a functional matrix membrane. The resulting white fiber membrane (i.e., B-GF) was sealed and stored in a glove box for later use to prevent hydrolysis.

[0108] (2) Preparation of composite all-solid polymer electrolyte membrane ex-SCPE:

[0109] First, polymer PEO (0.064 mol) and NaTFSI (0.004 mol) were dissolved in 20 mL of anhydrous acetonitrile to form a transparent homogeneous solution. The PEO / Na... + The molar ratio was controlled at 16:1. Subsequently, the functional matrix B-GF synthesized in step (1) was placed into a polytetrafluoroethylene mold, and the above solution was injected into B-GF. The acetonitrile was allowed to evaporate naturally, thereby obtaining a preliminary all-solid polymer electrolyte membrane ex-SCPE, which was then stored in an inert atmosphere.

[0110] (3) Vacuum hot-pressing and drying process for preparing all-solid polymer electrolyte SCPE:

[0111] The ex-SCPE prepared in step (2) was placed in a button-type polytetrafluoroethylene mold in a glove box. After applying a load of 20N, it was moved into a vacuum drying oven and dried at 60°C for 12 hours to finally obtain the all-solid polymer electrolyte SCPE.

[0112] Product testing:

[0113] like Figure 10 As shown, the boron-containing organic structures grown on the surface of B-GF prepared in Example 3 exhibit a relatively uniform distribution, but their morphology is not independent and regular.

[0114] The ionic conductivity, electrochemical window, and sodium ion transference number of the all-solid-state polymer electrolyte prepared in Example 3 were tested using the test method described in Example 1. The ionic conductivity of the all-solid-state polymer electrolyte prepared in Example 3 at 60°C was measured to be 2.98 × 10⁻⁶. -4 S cm -1 The electrochemical window is 5.38 V vs. Na. + / Na, the sodium ion transference number is 0.57.

[0115] Comparative Example 2

[0116] The preparation method of the all-solid-state polymer electrolyte SCPE is as follows:

[0117] (1) Preparation of functional matrix membrane B-GF:

[0118] 0.1 g of glass fiber membrane GF, 0.25 g of BDBA, and 10 mL of a 1:1 m-trimethylbenzene:1,4-dioxane solution were sealed in a Schlenk flask and mixed thoroughly. The resulting suspension was then rapidly frozen and evacuated at 77 K (LN2 bath), followed by sonication to thaw the mixture. This process was repeated twice to completely remove residual air. The prepared mixture was placed at 180 °C for 72 hours and washed with anhydrous acetone (treated with molecular sieves). The resulting fiber membrane was activated with anhydrous acetone for 24 hours and then dried in a vacuum oven at 180 °C for 12 hours.

[0119] The product prepared in Comparative Example 2 was observed using a scanning electron microscope, such as... Figure 13 As shown, due to the excessively high reaction temperature, boron-containing organic structures could not be grown in situ on the prepared B-GF surface.

[0120] Since the functional matrix membrane B-GF with boron-containing organic structure could not be successfully prepared, subsequent preparation and testing were discontinued.

[0121] Comparative Example 3:

[0122] The preparation method of the all-solid-state polymer electrolyte SCPE is as follows:

[0123] (1) Preparation of functional matrix membrane B-GF:

[0124] 0.1 g of glass fiber membrane GF, 0.25 g of BDBA, and 10 mL of a 1:1 m-trimethylbenzene:1,4-dioxane solution were sealed in a Schlenk flask and mixed thoroughly. The resulting suspension was then rapidly frozen and evacuated at 77 K (LN2 bath), followed by sonication to thaw the mixture. This process was repeated twice to completely remove residual air. The prepared mixture was placed at 90 °C for 72 hours and washed with anhydrous acetone (treated with molecular sieves). The resulting fiber membrane was activated with anhydrous acetone for 24 hours and then dried in a vacuum oven at 90 °C for 12 hours.

[0125] The product prepared in Comparative Example 3 was observed using a scanning electron microscope, such as... Figure 14 As shown, due to the excessively low reaction temperature, boron-containing organic structures could not be grown in situ on the prepared B-GF surface.

[0126] Since the functional matrix membrane B-GF with boron-containing organic structure could not be successfully prepared, subsequent preparation and testing were discontinued.

[0127] summary:

[0128] (1) By comparing Example 1 with Examples 2 and 3, it can be found that: when the reaction temperature in step (1) is controlled at 100-150℃ and the reaction time is 72 hours, the boron-containing organic structure can be grown in situ on the glass fiber surface, thus preparing a functional matrix film B-GF with a boron-containing organic structure. Among them, when the temperature is controlled at 120℃, the boron-containing polymer can grow in situ on the glass fiber surface well and exhibit a dense stacked structure on the glass fiber surface. When the temperature is 100℃ and 150℃, the prepared B-GF can also grow the boron-containing organic structure in situ on the glass fiber surface well, but the boron-containing organic structure exhibits an irregular morphology. At the same time, its electrochemical window, ionic conductivity, and sodium ion transference number were detected respectively, and the optimal reaction temperature was 120℃.

[0129] (2) By comparing Example 1 with Comparative Examples 2 and 3, it can be found that in Comparative Example 2, the reaction temperature was too high, and the prepared B-GF surface could not grow boron-containing organic structures in situ. In Comparative Example 3, even when the reaction temperature was lowered to 90°C, it was still impossible to prepare a functional matrix membrane B-GF with boron-containing organic structures.

[0130] Example 4

[0131] The preparation method of the all-solid-state polymer electrolyte SCPE is as follows:

[0132] (1) Preparation of functional matrix membrane B-GF:

[0133] 0.1 g of glass fiber membrane GF, 0.25 g of BDBA, and 10 mL of a 1:1 m-trimethylbenzene:1,4-dioxane solution were sealed in a Schlenk flask and sonicated at room temperature for 60 minutes. The resulting suspension was then rapidly frozen at 77 K (LN2 bath) and evacuated. The mixture was then thawed by sonication, and this process was repeated twice to completely remove residual air. The prepared mixture was placed at 120 °C for 24 hours to obtain an in-situ grown COF-1 fiber membrane. This membrane was washed with anhydrous acetone (treated with molecular sieves), activated with anhydrous acetone for 24 hours, and then dried in a vacuum oven at 120 °C for 12 hours to obtain the functional matrix membrane B-GF. The obtained functional matrix membrane B-GF was sealed and stored in a glove box for later use to prevent hydrolysis.

[0134] (2) Preparation of composite all-solid polymer electrolyte membrane ex-SCPE:

[0135] First, polymer PEO (0.064 mol) and NaTFSI (0.004 mol) were dissolved in 20 mL of anhydrous acetonitrile to form a transparent homogeneous solution. The PEO / Na... + The molar ratio was controlled at 16:1. Subsequently, the functional matrix membrane B-GF synthesized in step (1) was placed in a polytetrafluoroethylene mold, and the above solution was injected into the functional matrix membrane B-GF. The acetonitrile was allowed to evaporate naturally to obtain the composite all-solid polymer electrolyte membrane ex-SCPE, which was then stored in an inert atmosphere.

[0136] (3) Preparation of all-solid polymer electrolyte SCPE:

[0137] In a glove box, the composite all-solid polymer electrolyte membrane ex-SCPE prepared in step (2) is placed in a button-type polytetrafluoroethylene mold, and after applying a load of 20N, it is moved into a vacuum drying oven and dried at 60°C for 12 hours to finally obtain the all-solid polymer electrolyte SCPE.

[0138] Product testing:

[0139] like Figure 11 As shown, the boron-containing organic structure grown on the B-GF surface prepared in Example 4 exhibits a regular morphology, but its distribution is sparse and discontinuous.

[0140] The ionic conductivity, electrochemical window, and sodium ion transference number of the all-solid-state polymer electrolyte prepared in Example 4 were tested using the test method described in Example 1. The ionic conductivity of the all-solid-state polymer electrolyte prepared in Example 4 at 60°C was measured to be 3.86 × 10⁻⁶. -4 S cm -1 The electrochemical window is 5.56V vs. Na. + / Na, the sodium ion transference number is 0.53.

[0141] Example 5

[0142] The preparation method of the all-solid-state polymer electrolyte SCPE is as follows:

[0143] (1) Preparation of functional matrix membrane B-GF:

[0144] 0.1 g of glass fiber membrane GF, 0.25 g of BDBA, and 10 mL of a 1:1 m-trimethylbenzene:1,4-dioxane solution were sealed in a Schlenk flask and sonicated at room temperature for 60 minutes. The resulting suspension was then rapidly frozen at 77 K (LN2 bath) and evacuated. The mixture was then thawed by sonication, and this process was repeated twice to completely remove residual air. The prepared mixture was placed at 120 °C for 96 hours to obtain an in-situ grown COF-1 fiber membrane. This membrane was washed with anhydrous acetone (treated with molecular sieves), activated with anhydrous acetone for 24 hours, and then dried in a vacuum oven at 120 °C for 12 hours to obtain the functional matrix membrane B-GF. The obtained functional matrix membrane B-GF was sealed and stored in a glove box for later use to prevent hydrolysis.

[0145] (2) Preparation of composite all-solid polymer electrolyte membrane ex-SCPE:

[0146] First, polymer PEO (0.064 mol) and NaTFSI (0.004 mol) were dissolved in 20 mL of anhydrous acetonitrile to form a transparent homogeneous solution. The PEO / Na... + The molar ratio was controlled at 16:1. Subsequently, the functional matrix membrane B-GF synthesized in step (1) was placed in a polytetrafluoroethylene mold, and the above solution was injected into the functional matrix membrane B-GF. The acetonitrile was allowed to evaporate naturally to obtain the composite all-solid polymer electrolyte membrane ex-SCPE, which was then stored in an inert atmosphere.

[0147] (3) Preparation of all-solid polymer electrolyte SCPE:

[0148] In a glove box, the composite all-solid polymer electrolyte membrane ex-SCPE prepared in step (2) is placed in a button-type polytetrafluoroethylene mold, and after applying a load of 20N, it is moved into a vacuum drying oven and dried at 60°C for 12 hours to finally obtain the all-solid polymer electrolyte SCPE.

[0149] Product testing:

[0150] like Figure 12 As shown, the boron-containing organic structure grown on the B-GF surface prepared in Example 5 has a regular morphology, but it exhibits an excessively stacked distribution.

[0151] The ionic conductivity, electrochemical window, and sodium ion transference number of the all-solid-state polymer electrolyte prepared in Example 5 were tested using the test method described in Example 1. The ionic conductivity of the all-solid-state polymer electrolyte prepared in Example 5 at 60°C was measured to be 4.13 × 10⁻⁶. -4 S cm -1 The electrochemical window is 5.93 V vs. Na. + / Na, the sodium ion transference number is 0.61.

[0152] Comparative Example 4:

[0153] (1) Preparation of functional matrix membrane B-GF:

[0154] 0.1 g of glass fiber membrane GF, 0.25 g of BDBA, and 10 mL of a 1:1 m-trimethylbenzene:1,4-dioxane solution were sealed in a Schlenk flask and mixed thoroughly. The resulting suspension was then rapidly frozen and evacuated at 77 K (LN2 bath), followed by sonication to thaw the mixture. This process was repeated twice to completely remove residual air. The prepared mixture was placed at 120 °C for 12 hours and washed with anhydrous acetone (treated with molecular sieves). The resulting fiber membrane was activated with anhydrous acetone for 24 hours and then dried in a vacuum oven at 120 °C for 12 hours.

[0155] The product prepared in Comparative Example 4 was observed using a scanning electron microscope, such as... Figure 15 As shown, the reaction time was too short, and the boron-containing organic structure grown on the surface of the prepared B-GF was extremely sparse, which could not meet the actual preparation requirements. Therefore, subsequent preparation and testing were not carried out.

[0156] Comparative Example 5:

[0157] The preparation method of the all-solid-state polymer electrolyte SCPE is as follows:

[0158] (1) Preparation of functional matrix membrane B-GF:

[0159] 0.1 g of glass fiber membrane GF, 0.25 g of BDBA, and 10 mL of a 1:1 m-trimethylbenzene:1,4-dioxane solution were sealed in a Schlenk flask and mixed thoroughly. The resulting suspension was then rapidly frozen at 77 K (LN2 bath) and evacuated. The mixture was then thawed by sonication, and this process was repeated twice to completely remove residual air. The prepared mixture was placed at 120 °C for 108 hours and washed with anhydrous acetone (treated with molecular sieves). The resulting fiber membrane was activated with anhydrous acetone for 24 hours and then dried in a vacuum oven at 120 °C for 12 hours.

[0160] The product prepared in Comparative Example 5 was observed using a scanning electron microscope, such as... Figure 16 As shown, if the reaction time is too long, the boron-containing organic structure grown on the surface of the prepared B-GF will be destroyed, which will not meet the actual preparation requirements. Therefore, subsequent preparation and testing will not be carried out.

[0161] summary:

[0162] (1) By comparing Example 1 with Example 4 and Example 5, it can be found that: when the reaction temperature of step (1) is controlled at 120°C and the reaction time is 24-96 hours, the boron-containing organic structure can be grown in situ on the surface of glass fiber to prepare a functional matrix membrane B-GF with boron-containing organic structure. The electrochemical window, ionic conductivity and sodium ion transference number were detected respectively. The optimal reaction time is 72 hours.

[0163] (2) By comparing Example 1 with Comparative Examples 4 and 5, it can be found that in Comparative Example 4, the reaction time was too short, and the boron-containing organic structure grown on the surface of the prepared B-GF was extremely sparse, which could not meet the actual preparation requirements. In Comparative Example 5, the reaction time was extended to 108 hours. Due to the excessively long reaction time, the boron-containing organic structure grown on the surface of the prepared B-GF was destroyed.

[0164] Example 6

[0165] The preparation method of the all-solid-state polymer electrolyte SCPE is as follows:

[0166] (1) Preparation of functional matrix membrane B-GF:

[0167] 0.1 g of glass fiber membrane GF, 0.25 g of BDBA, and 10 mL of a 1:1 m-trimethylbenzene:1,4-dioxane solution were sealed in a Schlenk flask and sonicated at room temperature for 60 minutes. The resulting suspension was then rapidly frozen at 77 K (LN2 bath) and evacuated. The mixture was then thawed by sonication, and this process was repeated twice to completely remove residual air. The prepared mixture was placed at 120 °C for 72 hours to obtain an in-situ grown COF-1 fiber membrane. This membrane was washed with anhydrous acetone (treated with molecular sieves), activated with anhydrous acetone for 24 hours, and then dried in a vacuum oven at 120 °C for 12 hours to obtain the functional matrix membrane B-GF. The obtained functional matrix membrane B-GF was sealed and stored in a glove box for later use to prevent hydrolysis.

[0168] (2) Preparation of composite all-solid polymer electrolyte membrane ex-SCPE:

[0169] First, polymer PEO (0.064 mol) and NaTFSI (0.008 mol) were dissolved in 20 mL of anhydrous acetonitrile to form a transparent homogeneous solution. The PEO / Na... + The molar ratio was controlled at 8:1. Then, the functional matrix membrane B-GF synthesized in step (1) was placed in a polytetrafluoroethylene mold, and the above solution was injected into the functional matrix membrane B-GF. The acetonitrile was allowed to evaporate naturally to obtain the composite all-solid polymer electrolyte membrane ex-SCPE, which was then stored in an inert atmosphere.

[0170] (3) Preparation of all-solid polymer electrolyte SCPE:

[0171] In a glove box, the composite all-solid polymer electrolyte membrane ex-SCPE prepared in step (2) is placed in a button-type polytetrafluoroethylene mold, and after applying a load of 20N, it is moved into a vacuum drying oven and dried at 60°C for 12 hours to finally obtain the all-solid polymer electrolyte SCPE.

[0172] Product testing:

[0173] The ionic conductivity, electrochemical window, and sodium ion transference number of the all-solid-state polymer electrolyte prepared in Example 6 were tested using the test method described in Example 1. The ionic conductivity of the all-solid-state polymer electrolyte prepared in Example 6 at 60°C was measured to be 6.02 × 10⁻⁶. -4 S cm -1 The electrochemical window is 5.64 V vs. Na. + / Na, the sodium ion transference number is 0.42.

[0174] Example 7

[0175] The preparation method of the all-solid-state polymer electrolyte SCPE is as follows:

[0176] (1) Preparation of functional matrix membrane B-GF:

[0177] 0.1 g of glass fiber membrane GF, 0.25 g of BDBA, and 10 mL of a 1:1 m-trimethylbenzene:1,4-dioxane solution were sealed in a Schlenk flask and sonicated at room temperature for 60 minutes. The resulting suspension was then rapidly frozen at 77 K (LN2 bath) and evacuated. The mixture was then thawed by sonication, and this process was repeated twice to completely remove residual air. The prepared mixture was placed at 120 °C for 72 hours to obtain an in-situ grown COF-1 fiber membrane. This membrane was washed with anhydrous acetone (treated with molecular sieves), activated with anhydrous acetone for 24 hours, and then dried in a vacuum oven at 120 °C for 12 hours to obtain the functional matrix membrane B-GF. The obtained functional matrix membrane B-GF was sealed and stored in a glove box for later use to prevent hydrolysis.

[0178] (2) Preparation of composite all-solid polymer electrolyte membrane ex-SCPE:

[0179] First, polymer PEO (0.064 mol) and NaTFSI (0.0032 mol) were dissolved in 20 mL of anhydrous acetonitrile to form a transparent homogeneous solution. The PEO / Na... + The molar ratio was controlled at 20:1. Then, the functional matrix membrane B-GF synthesized in step (1) was placed in a polytetrafluoroethylene mold, and the above solution was injected into the functional matrix membrane B-GF. The acetonitrile was allowed to evaporate naturally to obtain the composite all-solid polymer electrolyte membrane ex-SCPE, which was then stored in an inert atmosphere.

[0180] (3) Preparation of all-solid polymer electrolyte SCPE:

[0181] In a glove box, the composite all-solid polymer electrolyte membrane ex-SCPE prepared in step (2) is placed in a button-type polytetrafluoroethylene mold, and after applying a load of 20N, it is moved into a vacuum drying oven and dried at 60°C for 12 hours to finally obtain the all-solid polymer electrolyte SCPE.

[0182] Product testing:

[0183] The ionic conductivity, electrochemical window, and sodium ion transference number of the all-solid-state polymer electrolyte prepared in Example 7 were tested using the test method described in Example 1. The ionic conductivity of the all-solid-state polymer electrolyte prepared in Example 7 at 60°C was measured to be 2.68 × 10⁻⁶. -4 S cm -1 The electrochemical window is 5.38V vs. Na.+ / Na, the sodium ion transference number is 0.55.

[0184] Comparative Example 6

[0185] The preparation method of the all-solid-state polymer electrolyte SCPE is as follows:

[0186] (1) Preparation of functional matrix membrane B-GF:

[0187] 0.1 g of glass fiber membrane GF, 0.25 g of BDBA, and 10 mL of a 1:1 m-trimethylbenzene:1,4-dioxane solution were sealed in a Schlenk flask and sonicated at room temperature for 60 minutes. The resulting suspension was then rapidly frozen at 77 K (LN2 bath) and evacuated. The mixture was then thawed by sonication, and this process was repeated twice to completely remove residual air. The prepared mixture was placed at 120 °C for 72 hours to obtain an in-situ grown COF-1 fiber membrane. This membrane was washed with anhydrous acetone (treated with molecular sieves), activated with anhydrous acetone for 24 hours, and then dried in a vacuum oven at 120 °C for 12 hours to obtain the functional matrix membrane B-GF. The obtained functional matrix membrane B-GF was sealed and stored in a glove box for later use to prevent hydrolysis.

[0188] (2) Preparation of composite all-solid polymer electrolyte membrane ex-SCPE:

[0189] First, polymer PEO (0.064 mol) and NaTFSI (0.016 mol) were dissolved in 20 mL of anhydrous acetonitrile to form a transparent homogeneous solution. The PEO / Na... + The molar ratio was controlled at 4:1. Then, the functional matrix membrane B-GF synthesized in step (1) was placed in a polytetrafluoroethylene mold, and the above solution was injected into the functional matrix membrane B-GF. During the experiment, it was found that due to the excessively high sodium salt ratio, the electrolyte membrane lacked self-support, and the composite all-solid polymer electrolyte membrane ex-SCPE could not be prepared. Therefore, subsequent preparation and testing steps were not performed.

[0190] Comparative Example 7

[0191] The preparation method of the all-solid-state polymer electrolyte SCPE is as follows:

[0192] (1) Preparation of functional matrix membrane B-GF:

[0193] 0.1 g of glass fiber membrane GF, 0.25 g of BDBA, and 10 mL of a 1:1 m-trimethylbenzene:1,4-dioxane solution were sealed in a Schlenk flask and sonicated at room temperature for 60 minutes. The resulting suspension was then rapidly frozen at 77 K (LN2 bath) and evacuated. The mixture was then thawed by sonication, and this process was repeated twice to completely remove residual air. The prepared mixture was placed at 120 °C for 72 hours to obtain an in-situ grown COF-1 fiber membrane. This membrane was washed with anhydrous acetone (treated with molecular sieves), activated with anhydrous acetone for 24 hours, and then dried in a vacuum oven at 120 °C for 12 hours to obtain the functional matrix membrane B-GF. The obtained functional matrix membrane B-GF was sealed and stored in a glove box for later use to prevent hydrolysis.

[0194] (2) Preparation of composite all-solid polymer electrolyte membrane ex-SCPE:

[0195] First, polymer PEO (0.064 mol) and NaTFSI (0.00256 mol) were dissolved in 20 mL of anhydrous acetonitrile to form a transparent homogeneous solution. The PEO / Na... + The molar ratio was controlled at 25:1. The functional matrix membrane B-GF synthesized in step (1) was then placed into a polytetrafluoroethylene mold, and the above solution was injected into the functional matrix membrane B-GF. During the experiment, it was found that due to the excessively low sodium salt ratio, the polymer phase viscosity was too high, making it impossible to fully infuse the prepared B-GF functional matrix membrane. Therefore, the composite all-solid polymer electrolyte membrane ex-SCPE could not be obtained, and subsequent preparation and testing steps were discontinued.

[0196] summary:

[0197] (1) By comparing Example 1 with Examples 6 and 7, it can be found that: EO / Na in step (2) + The molar ratio has a significant impact on product performance. Generally, when the sodium salt ratio is low (Example 7), the electrochemical window, ionic conductivity, and sodium ion transference number of the prepared all-solid polymer electrolyte are all lower than those in Example 1. As the sodium salt ratio increases, the electrochemical window, ionic conductivity, and sodium ion transference number all increase to some extent. When the EO / Na + When the molar ratio reaches 8:1 (Example 6), it exhibits high ionic conductivity, but the electrochemical window and sodium ion transference number are reduced. Overall, the optimal EO / Na ratio is... + The molar ratio is 16:1.

[0198] (2) By comparing Example 1 with Comparative Examples 6 and 7, it can be found that: an excessively low sodium salt ratio results in an excessively high polymer phase viscosity, which cannot be fully infused into the prepared B-GF functional matrix membrane, thus failing to obtain a uniform solid electrolyte membrane and failing to meet the requirements of practical applications. Conversely, when the sodium salt ratio is too high (EO / Na...),... + When the molar ratio reaches 4:1, the prepared solid electrolyte membrane lacks self-support and cannot meet the needs of practical applications.

[0199] Comparative Example 1: Preparation of all-solid-state polymer electrolyte CPE

[0200] The preparation method of all-solid-state polymer electrolyte CPE is as follows:

[0201] (1) Preparation of composite all-solid polymer electrolyte membrane ex-CPE:

[0202] First, polymer PEO (0.064 mol) and NaTFSI (0.04 mol) were dissolved in 20 mL of anhydrous acetonitrile to form a transparent homogeneous solution. The PEO / Na... + The molar ratio was controlled at 16:1. Then, the pure glass fiber membrane GF was placed into a polytetrafluoroethylene mold, and the above solution was injected into GF. The acetonitrile was allowed to evaporate naturally, thus obtaining a preliminary all-solid polymer electrolyte membrane ex-CPE, which was stored in an inert atmosphere.

[0203] (2) Preparation of all-solid polymer electrolyte CPE by vacuum hot pressing and drying treatment:

[0204] The ex-SCPE prepared in step (1) was placed in a button-type polytetrafluoroethylene mold in a glove box. After applying a load of 20N, it was moved into a vacuum drying oven and dried at 60°C for 12 hours to finally obtain the all-solid polymer electrolyte CPE.

[0205] Performance testing:

[0206] The ionic conductivity, electrochemical window, and sodium ion transport number of the all-solid-state polymer electrolyte prepared in Comparative Example 1 were tested using the test method described in Example 1. The room-temperature ionic conductivity of this electrolyte was measured to be 1.12 × 10⁻⁶. -4 S cm -1 The electrochemical window is 5.75V vs. Na. + / Na, sodium ion transference number is 0.22.

[0207] Application Example 1

[0208] This embodiment uses the all-solid-state polymer electrolyte prepared in Example 1 to assemble an all-solid-state sodium-ion battery, and tests the battery's electrochemical performance, as detailed below:

[0209] (1) Preparation of positive electrode sheet: The positive active material powder of sodium vanadium phosphate Na3V2(PO4)3 is uniformly mixed with the conductive agent Super P and the binder PVDF in a mass ratio of 80:10:10. An appropriate amount of N-methylpyrrolidone NMP solution is added. The mixture is stirred and ultrasonically prepared in a dry environment at room temperature to form a uniform slurry. The slurry is then coated onto a dry and flat aluminum foil, transferred to a vacuum drying oven for drying, and finally cut to size for use.

[0210] (2) Preparation of negative electrode: Sodium metal is used as the negative electrode.

[0211] Using Na3V2(PO4)3 prepared in step (1) as the positive electrode, metallic sodium as the negative electrode, and the all-solid polymer electrolytic SCPE prepared in Example 1 as the electrolyte, a 2032 button battery was assembled in a glove box and denoted as battery 1.

[0212] Performance testing: Battery charge / discharge tests were conducted at room temperature, with a test voltage range of 2.5V to 3.8V. The test results are as follows: Figure 13 and Figure 14 As shown. Figure 13 Battery 1 was demonstrated at a current density of 100 mA g. -1 The charge / discharge curves for the first and 100th cycles are shown in the graph. It can be seen from the graph that the specific capacity of battery 1 during the first discharge cycle is 114.3 mAh g. -1 The coulombic efficiency is 97.4%, and the capacity retention rate after 100 cycles is 94.9%, indicating that the battery has good reversibility and cycle stability.

[0213] Application Example 2

[0214] This embodiment uses the all-solid-state polymer electrolyte prepared in Comparative Example 1 to assemble an all-solid-state sodium-ion battery, and tests the battery's electrochemical performance, as detailed below:

[0215] (1) Preparation of positive electrode sheet: The positive electrode active material powder of sodium vanadium phosphate Na3V2(PO4)3 is uniformly mixed with the conductive agent Super P and the binder PVDF in a mass ratio of 80:10:10. An appropriate amount of N-methylpyrrolidone NMP solution is added, and the mixture is ground and stirred into a uniform slurry in a dry environment at room temperature. The slurry is then coated onto a dry and flat aluminum foil, transferred to a vacuum drying oven for drying, and finally cut to size for use.

[0216] (2) Preparation of negative electrode: Sodium metal is used as the negative electrode.

[0217] Using Na3V2(PO4)3 prepared in step (1) as the positive electrode, metallic sodium as the negative electrode, and the all-solid polymer electrolyte CPE prepared in Comparative Example 1 as the electrolyte, a 2032 button battery was assembled in a glove box and denoted as battery 2.

[0218] Performance Testing: Battery charge / discharge tests were conducted at room temperature, with a test voltage range of 2.5V to 3.8V. The battery performed well at a current density of 100mA / g. -1 The initial discharge specific capacity is only 104.0 mAh g. -1 The coulomb efficiency is 93.1%, and the capacity retention rate is only 77% after 100 cycles.

[0219] analyze:

[0220] (1) Comparing Example 1 with Comparative Example 1, it can be found that:

[0221] In Comparative Example 1, a glass fiber membrane with an in-situ grown boron-containing organic structure was used as the perfusion framework. It was found that the all-solid polymer electrolyte prepared by it exhibited poorer electrochemical performance compared with Example 1, such as a significant reduction in electrochemical window, ionic conductivity, and sodium ion transference number.

[0222] (2) Comparing Application Example 1 and Application Example 2, it can be found that:

[0223] The battery 1 prepared using the all-solid-state polymer electrolyte prepared in Example 1 has significantly improved charge-discharge performance and cycle performance compared with the battery 2 prepared using the all-solid-state polymer electrolyte prepared in Comparative Example 1.

[0224] The exemplary embodiments of the present invention have been described above. However, the present invention is not limited to the above embodiments. Any modifications, equivalent substitutions, improvements, etc., made by those skilled in the art within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. An all-solid-state polymer electrolyte, characterized in that: The all-solid polymer electrolyte comprises a functional matrix, a polymer matrix, and a sodium salt, wherein the functional matrix comprises a boron-containing organic structure and a porous support, and the boron-containing organic structure has abundant Lewis acid sites; The functional matrix is ​​a porous support modified with a boron-containing organic structure, which is obtained by in-situ growing the boron-containing organic structure on the surface of the porous support. The boron-containing organic structure is selected from any of the compounds having the following structural formulas: 、 、 、 。 2. The all-solid-state polymer electrolyte according to claim 1, characterized in that: The polymer matrix includes ethoxy groups, and the polymer matrix is ​​combined with sodium salt and then infused into the functional matrix.

3. The all-solid-state polymer electrolyte according to claim 1, characterized in that: The polymer matrix is ​​selected from at least one of polyethylene oxide (PEO) and polyphenylene oxide (PPO).

4. The all-solid-state polymer electrolyte according to claim 1, characterized in that: The sodium salt is selected from at least one of NaClO4, NaPF6, NaFSI, NaTFSI, and NaBF4.

5. The all-solid-state polymer electrolyte according to claim 1, characterized in that: The porous support is selected from at least one of glass fiber membrane, polyimide membrane, cellulose nonwoven membrane, polyethylene terephthalate film, and polyimide membrane.

6. A method for preparing the all-solid-state polymer electrolyte according to claim 1, characterized in that: A functional matrix is ​​prepared by solution in-situ polymerization using a porous support as a substrate. The polymer matrix and a sodium salt mixture are then infused into the functional matrix, and finally, a fully solid polymer electrolyte is obtained through vacuum hot-pressing and drying. The process includes the following steps: (1) Preparation of functional matrix: Boron-containing monomers and ligands are mixed into a solvent to form a precursor mixture. The porous support is then immersed in the precursor mixture and polymerized in situ to obtain a porous support modified with a boron-containing organic structure, which is the functional matrix. In step (1), the reaction temperature of the in-situ polymerization is 100℃~150℃, and the reaction time of the in-situ polymerization is 24h~96h; (2) Preparation of composite all-solid polymer electrolyte membrane: The polymer matrix and sodium salt are prepared into a solution in a certain proportion and filled into the functional matrix obtained in step (1) by solution perfusion method to obtain a composite all-solid polymer electrolyte membrane. In step (2), the polymer matrix is ​​PEO or PPO, the sodium salt is selected from NaClO4, NaPF6, NaFSI, NaTFSI or NaBF4, and the ratio of polymer matrix to sodium salt is 8 to 20:

1. (3) Vacuum hot pressing drying treatment: The composite all-solid polymer electrolyte membrane prepared in step (2) is placed in a button mold and subjected to vacuum drying to obtain the all-solid polymer electrolyte.

7. The method for preparing an all-solid-state polymer electrolyte according to claim 6, characterized in that: In step (1), the boron-containing monomer is selected from any one of 1,4-phenyldiboronic acid (BDBA), biphenyl diboronic acid (BPDA), 1,3,5-phenyltriboronic acid (BTBA), and 1,3,5-phenyl ester (4-phenylboronic acid) (BTPA).

8. The method for preparing an all-solid-state polymer electrolyte according to claim 6, characterized in that: In step (1), the ligand is selected from any one of 1,4-phenyldiboronic acid BDBA and 2,3,6,7,10,11-hexahydroxytriphenylHHTP.

9. The method for preparing an all-solid-state polymer electrolyte according to claim 6, characterized in that: In step (1), the solvent is a mixed solution of m-trimethylbenzene and 1,4-dioxane, and the volume ratio of m-trimethylbenzene to 1,4-dioxane is 0.5-1.5:0.5-1.

5.

10. The method for preparing an all-solid-state polymer electrolyte according to claim 6, characterized in that: In step (1), the product obtained by in-situ polymerization is washed, activated, vacuum dried, and then sealed and stored. The washing solvent is anhydrous acetone or anhydrous acetonitrile, and the washing is performed 1-4 times. The activation solvent is anhydrous acetone, and the activation time is 12-36 hours. The vacuum drying temperature is 100℃-150℃, and the vacuum drying time is 12-36 hours. The prepared functional matrix is ​​sealed and stored in an inert atmosphere to prevent hydrolysis.

11. The method for preparing an all-solid-state polymer electrolyte according to claim 6, characterized in that: In step (3), the load pressure of the snap mold is 5-50N, and the vacuum drying temperature is 50-80℃.

12. The application of the all-solid-state polymer electrolyte of claim 1 in the preparation of an all-solid-state sodium-ion battery.